Pengaruh pemberian fraksi air kulit buah delima (Punica granatum L) terhadap jumlah duktus payudara tikus yang diovariektomi - Sunarmi, Sunarmi; Bahtiar, Anton; Wuyung, Puspita Eka (Jurnal Farmasi Indonesia, 2016)
Pomegranate (Punica granatum L.) is known to have estrogenic activity. Pomegranate peel proven to increase the number of osteoblasts and increases bone density. This study aims to determine the potential of the water fraction of the pomegranate peel as natural Selective Estrogen Receptor Modulators (SERMs) through histological mammary in ovariectomized rats. Ovariectomy method used as a model representing menopause, conducted on 42 rats female Sprague Dawley strain aged 50 days were divided into 7 groups: Sham, OVX, and a group of OVX, each getting estradiol, tamoxifen and fractions water pomegranate peel dose of 50, 100, and 200 mg/kg BW. The results obtained showed water fraction of pomegranate peel did not show any increase in volume and number of mammary ducts.